SEBUAH TINJAUAN LITERATUR TERHADAP PENELITIAN RELEVANSI NILAI SETELAH ADOPSI IFRS - Manuela, Angel; Septiani, Leny; Wulan, Ariska Berlian Nur; Fitria, Salsha Ramadhani Nur (Jurnal Ilmiah Wahana Akuntansi, 2021)
The purpose of this study is to provide an overview of value relevance (VR) by reviewing and analyzing research on VR that has been conducted mainly in Indonesia. The structured literature review (SLR) method was used to track the development of the VR literature. The keywords used in this study are “adopsi IFRS”, "informasi akuntansi", “reelvansi nilai” and "value relevance". The use of keyword “informasi akuntansi” is to limit the scope of the VR literature explored in the accounting context. Most of the research reviewed is from Indonesia and is indexed by SINTA, but there are also studies from Turkey and Argentina. This study examines theories related to VR and especially discusses VR after the adoption of IFRS in Indonesia.